Load Frequency Control of Renewable Penetrated Multi Area Power System with Intelligent Techniques - Jood, Pankaj (My University, 2023)
In this work, the performance of a neuro-fuzzy controller is analyzed for load frequency control (LFC) problem in modern power systems. The recent changes in power system structure due to inclusion of renewable energy resources and energy storage devices have made their operation and control a difficult task. It has become challenging for a conventional controller to handle such type of power systems with increased levels of uncertainty and intermittency. Intelligent controllers because of their adaptable characteristics may be helpful in managing these systems. Moreover, their performance is yet to be evaluated in the presence of renewable resources and considering system non-linearities simultaneously. In order to evaluate the performance of intelligent controllers in this environment, a neuro-fuzzy based LFC technique has been applied. In this research work, the design and simulation of an adaptive neuro fuzzy inference system (ANFIS) based controller is presented for a power network. The training data set for the ANFIS controller is obtained by tuning a proportional integral (PI) controller using bode plot approach for a test case system. An interconnected two-area power system is modeled with all its non-linearities such as boiler dynamics, generation rate constraints, governor dead band and time delay. The system is integrated with wind and solar resources in the form of a time series data with a resolution of one second. The impact of these two renewable energy resources on the frequency response of the power system is analyzed in terms of maximum overshoot (MP) and settling time (ts). The multiple scenarios of wind and solar penetration levels are considered. Further, the energy storage technologies are utilized for improving the primary frequency control in complex electrical systems. The capacitive energy storage (CES), battery energy storage (BES), and superconducting magnetic energy storage (SMES) are considered for the study. On the basis of peak overshoot and settling time, the performance of these energy storage devices is compared. The load on the power system shifts significantly throughout the span of a day, and as a result, several generation schedules are planned for thermal power plants. The turbine time constants and the power fractions are two parameters that are typically used to model steam turbines. The parameters of the steam turbine dynamic model are sensitive to these changes and therefore fluctuate along with the generation schedules of the plant. The performance of the ANFIS controller is assessed for three generation levels i.e. 30, 50 and 100%. In addition to above work, the automatic generation control (AGC) in a two-area power system is also modeled and analyzed using a discrete controller. The outputs of a generating unit are typically adjusted in discrete steps using the control pulses. The following are the findings of the research work: • The dynamic performance of ANFIS controller in two-area renewable penetrated power system has been validated by assessing two indices namely peak overshoot and settling time, which have been found to be better as compared to that of fixed gain PI controller. • The combined performance of the ANFIS controller and storage unit is more effective. In the presence of storage units, the reduction in settling time is significant as compared to the reduction in peak overshoot. Within the storage units, the best performance was obtained with the help of the SMES unit. • Real time analysis of AGC system relies upon the sampling period of area control error (ACE). Improper selection of sampling period degrades the performance of the system or causes system instability. An analysis of controller performance in discrete mode is presented in presence of renewable resources.
Keywords: Load Frequency Control; Renewable Penetration; Multi Area Power System; Intelligent Techniques; ANFIS controller